Powder technology : handling and operations, process instrumentation, and working hazards - Masuda, Hiroaki, 1943-; Higashitani, Kō, 1944-; Yoshida, Hideto, 1952- (CRC Press/Taylor & Francis, 2007)
Drawing from the third edition of the bestselling Powder Technology Handbook, this book concentrates on handling methods and unit operations for powder and particle processing techniques. Itexamines the purpose and factors involved in each process-including planning, equipment, measurements, and other necessary considerations. This book carefully incorporates the progressive work and vision of new authors while retaining the concepts that continue to promote innovative research and applications. In addition to detailing the purpose and implementation of processes including kneading,